A theoretical study of fullerene-ferrocene hybrids - Kang, Hong Seok (Journal of computational chemistry, 2007)
Using density functional theory within the generalized gradient approximation, I analyzed the electronic structure of a C(60)-ferrocene hybrid [= C(60) (*) FeCp] around HOMO in comparison with that of ferrocene, where C(60) (*) and Cp denote C(60)(CH(3))(5) and a cyclopentadienyl ring. HOMO-LUMO gap is significantly smaller than that of ferrocene because of the intervention of pi(C(60) (*)) states below LUMO. In addition, geometrical and electronic structures of NC(60) (*) FeCp are also investigated. I find that there are two isomers with the energy difference of 0.13 eV. In one of the two, the encased nitrogen atom is located at the center of the fullerene cage. The Fe atom is eta(5)-coordinated to both Cp and R*, where R* is a five-membered ring of C(60) (*) cage. On the other hand, the atom is coordinated to R* with eta(4)-hapticity, and the nitrogen atom is bonded to a carbon atom of the R* ring in the other isomer. Upon the isomerization between the two isomers, there occurs a partial transfer of spin density between the nitrogen and Fe atoms as well as the creation and breaking of a C-N bond